2005
DOI: 10.1063/1.2046710
|View full text |Cite
|
Sign up to set email alerts
|

Decaying grid-generated turbulence in a rotating tank

Abstract: The decay of initially three-dimensional homogeneous turbulence in a rotating frame is experimentally investigated. Turbulence is generated by rapidly towing a grid in a rotating water tank, and the velocity field in a plane perpendicular to the rotation axis is measured by means of particle image velocimetry. During the decay, strong cyclonic coherent vortices emerge, as the result of enhanced stretching of the cyclonic vorticity by the background rotation, and the selective instability of the anticyclonic vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
147
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(170 citation statements)
references
References 49 publications
20
147
3
Order By: Relevance
“…The breaking of asymmetry between cyclonic and anticyclonic vortices, which has been observed both in experiments [15,25,[28][29][30] and in numerical simulations [20,31,32], is a distinctive feature of rotating turbulent flows. Here we are interested to investigate how this asymmetry is influenced both by the rotation and the confinement of the flow.…”
Section: Cyclonic-anticyclonic Asymmetrymentioning
confidence: 99%
“…The breaking of asymmetry between cyclonic and anticyclonic vortices, which has been observed both in experiments [15,25,[28][29][30] and in numerical simulations [20,31,32], is a distinctive feature of rotating turbulent flows. Here we are interested to investigate how this asymmetry is influenced both by the rotation and the confinement of the flow.…”
Section: Cyclonic-anticyclonic Asymmetrymentioning
confidence: 99%
“…More recently, Baroud et al (2003) investigated turbulent water jets in a rotating annulus at Re λ = 360, and found the turbulent flow to be highly intermittent, independent of the Rossby number. Morize, Moisy, and Rabaud performed several experiments of decaying rotating turbulence in large and small facilities (Morize et al, 2005, Morize and Moisy, 2006, Moisy et al, 2010, and described in details some aspects of the coupling between the inertial wave pattern and the decaying turbulent field using high-resolution PIV. Accurate visualisations by means of reflective flakes of the formation and evolution of columnar eddies in rotating turbulence were performed by Davidson et al (2006).…”
Section: Brief Overview Of Previous Studies Of Rotating Turbulencementioning
confidence: 99%
“…Numerical simulations have shown that the faster growth of certain integral length scales is also related to the inhibited energy cascade. [21][22][23] Among the most recent experimental studies are those by Baroud et al, 13,14 Morize and co-workers, 15,24 and by Davidson an co-workers. 16, 17 Baroud and co-workers studied the flow in a rotating annulus with forcing created by pumping water into ͑out of͒ the annulus through an inner ͑outer͒ ring of holes on the bottom of the annulus.…”
Section: Introductionmentioning
confidence: 99%
“…In laboratory experiments reported in Ref. 15 initially isotropic homogeneous turbulence is generated by rapidly towing a grid in a rotating liquid-filled container. During the decay, strong cyclonic coherent vortices emerge as the result of enhanced stretching of the cyclonic vorticity by the background rotation and the selective instability of the anticyclonic vorticity by the Coriolis force.…”
Section: Introductionmentioning
confidence: 99%